Ulrich Bonerius - A Swiss-German Boccaccio? Fourteenth-century literary synergies - Classen, Albrecht (Neuphilologische Mitteilungen, 2022)
The Dominican Priest from Bern, Ulrich Bonerius, composed his collection of fables, Der Edelstein, at exactly the same time when Boccaccio created his collection of tales, Decameron, 1350. Even though there is no direct evidence of any kind of personal contacts between these two poets, the strong similarities between both works in formal and conceptual terms prove to be striking. This article illustrates the reasons why we would be justified to call Bonerius, more than just playfully, a German-language Boccaccio, since he created the first major compilation of narratives (in verse), framed by a prologue and an epilogue, in the history of late medieval German literature. While Boccaccio has ten story-tellers entertain each other over ten days (ten stories per day = 100) reflecting on eroticism, love, adventures, or anti-clericalism, Bonerius offers one hundred didactic fables illustrating human failings, shortcomings, and vices. Both contemporaries thus aimed at criticizing and improving their society through surprisingly similar literary means. Bonerius thus emerges as one of the most important fourteenth-century poets in the German tongue who deserves to be placed close to Boccaccio.